The empirical performance of humane entrepreneurship. Issue 1 (2nd January 2022) - El Tarabishy, Ayman; Hwang, Won-Sik; Enriquez, John Laurence; Kim, Ki-Chan
ABSTRACT: Employing a theoretical framework to answer the issues faced by SMEs, this article uses new models of humane entrepreneurship, a business model that invests in human capital as the chief source of innovation. While traditional entrepreneurship focuses on innovation achieved through investments in new business opportunities, risk-taking, and proactivity, humane entrepreneurship focuses on how investment in the workforce can achieve enterprise-type innovation. This study aims to demonstrate the validity of people-centric small and medium-sized enterprise policy development by examining the effect on innovation of humane entrepreneurship.